2022
DOI: 10.3389/fonc.2022.901475
|View full text |Cite
|
Sign up to set email alerts
|

GCLDNet: Gastric cancer lesion detection network combining level feature aggregation and attention feature fusion

Abstract: BackgroundAnalysis of histopathological slices of gastric cancer is the gold standard for diagnosing gastric cancer, while manual identification is time-consuming and highly relies on the experience of pathologists. Artificial intelligence methods, particularly deep learning, can assist pathologists in finding cancerous tissues and realizing automated detection. However, due to the variety of shapes and sizes of gastric cancer lesions, as well as many interfering factors, GCHIs have a high level of complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In their study, Shi et al (30) researched to develop an automated method for identifying regions impacted by gastric cancer in photographs of gastric histopathology samples. The researchers employed a convolutional neural network (CNN) decoder in their methodology to extract relevant features and incorporate an attention mechanism.…”
Section: Related Workmentioning
confidence: 99%
“…In their study, Shi et al (30) researched to develop an automated method for identifying regions impacted by gastric cancer in photographs of gastric histopathology samples. The researchers employed a convolutional neural network (CNN) decoder in their methodology to extract relevant features and incorporate an attention mechanism.…”
Section: Related Workmentioning
confidence: 99%
“…A hierarchical feature aggregation structure is designed in the decoder, which can effectively fuse deep and shallow features. The attention feature fusion module is introduced to accurately locate the lesion area, and the attention features of different scales are fused to obtain rich lesion discrimination information ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding pneumonia, many studies have considered the automatic detection of COVID-19 pneumonia [ 9 ] and predicted the severity of the disease [ 10 ]. In a study using non-lung histopathology specimens, Shi et al proposed a method for the automatic detection of gastric cancer regions in images of gastric histopathology specimens using a CNN decoder for feature extraction and an attention mechanism [ 11 ]. The evaluation using two datasets showed that it has a satisfactory detection agreement.…”
Section: Introductionmentioning
confidence: 99%